Hidden in plain sight: findings from a survey on the multi-major professional writing course. Issue 3 (3rd July 2018) - Read, Sarah; Michaud, Michael
ABSTRACT: In this article, the authors report on findings from a survey of writing instructors who teach the multimajor professional writing course (MMPW) across diverse institutional contexts. The authors marshal these findings to advance a series of arguments about the situation of the MMPW course in U.S. higher education.